TANGGUNG JAWAB ORANG TUA TERHADAP ANAK SEBAGAI PENGEDAR NARKOTIKA - Ardhicka Dwinanda Lutgianto; Wayan Made (Gapenas Publisher, 2023)
The illicit circulation of narcotics involving children as dealers is one of the national problems faced by the government in tackling the dangers of narcotics. This problem becomes complex because of criminal sanctions against children as narcotics dealers. On the other hand, there are aspects of prevention and parental obligations in the education and supervision of children mandated by law. This study aims to find the rationale for parents to be held criminally responsible for children as narcotics dealers, and to formulate prescriptions for the parameters of parental criminal responsibility for children as narcotics dealers in the future. Children must be given protection including legal protection. The aspect of justice is reflected in the legal obligations of parents to children which must be carried out with full responsibility. The aspect of interest is shown by the strategic role of children in ensuring the continuity of the existence of the nation and state in the future. The sociological basis is shown by 4 (four) facts regarding social phenomena including local wisdom, regarding the need to regulate criminal responsibility of parents towards children as narcotics dealers. In the juridical basis, there are regulations regarding the obligations of parents towards children, but the criminal responsibility of parents when a child becomes a narcotics dealer has not been regulated. In this study, there are 4 (four) cumulative parameters that can be used to determine the criminal responsibility of parents for children as narcotics dealers, namely: 1. Age limit for children; 2. Obligations of parents towards children; 3. Children under the effective supervision of parents, including: a. De facto supervision, b. Parents' actions in terms of knowing or duly suspecting a child of being a narcotics dealer, and c. Children live with parents; 4. Narcotics Category I and II are seen from the high dependency syndrome and the inclusion of the death penalty for certain crimes in the group referred to. This dissertation research has proven that the concept of substitute criminal responsibility for parents has the prospect of encouraging parents to carry out their obligations in supervising and preventing children from becoming narcotics dealers, and can be implemented in the narcotics law that is being revised by the government